Reducing traffic congestion through low-cost traffic light coordination: a study in a medium-sized city - Valeriano Mamani, Wilmer Diego (2025)
Urban growth and vehicular expansion in cities have progressively reduced the level of service on main roads, affecting mobility, energy efficiency, and road safety. In this context, the study aimed to evaluate vehicular congestion along an urban corridor in the city of Moquegua, Peru, classified as an intermediate city. The methodology was based on field measurements, including vehicle counts, travel times, and intersection delays, complemented by the application of the Highway Capacity Manual (HCM) criteria to determine the Level of Service (LOS). The results showed that the corridor initially presented a Level of Service E, with speeds ranging from 23 to 28 km/h and an average delay of 52 s/veh. After implementing traffic signal coordination and cycle time adjustments, the Level of Service improved to C, with a 40.4 % reduction in delays and a 36 % increase in operating speed. Additionally, there was a 10 % reduction in CO₂ emissions and an 11 % decrease in fuel consumption, demonstrating the effectiveness of low-cost operational strategies in promoting more efficient and sustainable urban mobility.